War in #alleyesonrafah meme: Unraveling the Implications of the Palestine-Israel Conflict on Young-Children - Azhar, Romaito; Rifmayanti, Cici; Harahap, Aihani Rahmayani; Ikhsan, Muhammad; Akbar, Rahmad Ade (IAS Journal of Localities, 2024)
The dissemination of Palestinian conflict issues on Instagram social media, goes beyond simply being a form of informative communication practice, it also describes the situation and latent dangers of the conflict’s implications for vulnerable groups. However, this context tends to be neglected in scientific discussions. This study also focuses on explaining and reflecting on the latent dangers of the implications of the Palestine-Israel conflict for children as a vulnerable group on Instagram. By using a qualitative descriptive case study approach, this study shows three important findings. First, the latent danger of the Palestinian-Israeli conflict, aside from claiming the lives of many children who were victims, quite a few children also lost their relatives and friends who were in the conflict area. Second, the latent danger of the Palestinian-Israeli conflict, aside depriving depriving children of their right to get a decent place to live, it has also destroyed the living environment in refugee camps for children in conflict areas. Third, the latent danger of the Palestinian-Israeli conflict, aside from causing children to lose their fathers and mothers, also causes quite a few of children to lose their entire family members in conflict areas. This study also recommends the importance of discussing the issues of the Palestinian-Israeli conflict which are disseminated on Instagram by using more varied hashtags.